Culture, goal orientation and achievement of vocational college students - Lin, Xuefei; Lei, Peiyao; Tan, Qi; Xiong, Bin (Frontiers in Psychology, 2025)
IntroductionThis study explored the relationship between cultural values, goal orientation, and mathematics achievement in mainland China.MethodsStructural equation modelling was used to analyze data collected from 1,004 first-year students of four majors in higher vocational colleges. This study adopted a four-dimensional goal orientation, including achievement (i.e., students’ mastery, performance-approach, and performance-avoidance) and society (i.e., family instrumental support goal orientation, and family emotional support goal orientation) to describe Chinese students’ motivation.ResultsThe results indicated that mathematics achievement was positively related to mastery goal orientations and negatively related to the performance-avoidance goal orientation. Family recognition through achievement was found to positively predict the students’ mastery, performance-approach, performance-avoidance, while conformity to norms was negatively linked to performance-approach orientations. Collectivism, on the other hand, was positively related to adopting the family support goal orientation and to mastery goal orientations, performance-approach. Nevertheless, emotional self-control was positively associated with students’ mastery. Humility was positively related to performance-approach orientations, family instrumental support goal orientation and family emotional support goal orientation. It also had a direct positive predictive effect on mathematics achievement. The results of the bootstrap analyses further confirmed the mediating role of goal orientation in the relationship between cultural values and mathematics achievement: there were positive indirect paths through the mastery orientations, and negative indirect paths through the performance-avoidance goal orientation.DiscussionPotential explanations for the findings are discussed. This will help reveal the group specificity of cultural values and goal orientation theory, thereby supplementing the contextual adaptability of the theory.